2000
DOI: 10.1038/sj.bjp.0703181
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of human sulphonylurea receptor SUR1 and inward rectifier K+ channel Kir6.2 combination expressed in HEK‐293 cells

Abstract: 1 The pharmacological properties of K ATP channels generated by stable co-expression of the sulphonylurea receptor SUR1 and the inwardly rectifying K + channel Kir6.2 were characterized in HEK-293 cells. 2 [ 3 H]-Glyburide (glibenclamide) bound to transfected cells with a B max value of 18.5 pmol mg 71 protein and with a K D value of 0.7 nM. Speci®c binding was displaced by a series of sulphonylurea analogues with rank order potencies consistent with those observed in pancreatic RINm5F insulinoma and in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…In particular, A-312110 did not show significant displacement of [ 3 H]glyburide, a high-affinity radioligand for SUR1-containing K ATP channels. Additional [ 3 H]glyburide studies confirmed that A-312110 did not displace the high-affinity SUR1 binding to rat brain membranes, a preparation in which high-affinity binding interactions correlate well with those derived from recombinant SUR1 channels (Gopalakrishnan et al, 2000). Under similar conditions, unlabeled gluburide displaced binding with a K i value of 0.28 Ϯ 0.09 nM (n H ϭ 0.72 Ϯ 0.15; n ϭ 3; Fig.…”
Section: Characterization Of A-312110 As a K Atp Channelsupporting
confidence: 52%
“…In particular, A-312110 did not show significant displacement of [ 3 H]glyburide, a high-affinity radioligand for SUR1-containing K ATP channels. Additional [ 3 H]glyburide studies confirmed that A-312110 did not displace the high-affinity SUR1 binding to rat brain membranes, a preparation in which high-affinity binding interactions correlate well with those derived from recombinant SUR1 channels (Gopalakrishnan et al, 2000). Under similar conditions, unlabeled gluburide displaced binding with a K i value of 0.28 Ϯ 0.09 nM (n H ϭ 0.72 Ϯ 0.15; n ϭ 3; Fig.…”
Section: Characterization Of A-312110 As a K Atp Channelsupporting
confidence: 52%
“…The assay of KATP channel openers, which may also be available for HTS, has been recently developed by applying 96-well FIPR analysis and DiBAC4(3) to cultured smooth muscle cells (12) and to HEK293 cells co-expressing recombinant Kir 6.X and SUR X (13). The same techniques could be available for the assay of BK channel openers.…”
Section: +mentioning
confidence: 99%
“…The limited use of voltage-sensitive dyes for the measurements of cellular electrical activities in HTS for agents acting on ion channels has been pointed out from the aspects of recording stability, temporal and voltage resolution, and/ or optical artifacts (10). Although a bis-oxonol fluorescent dye, bis-(1,3-dibutylbarbituric acid)-trimethine oxonol (DiBAC4(3)), which responds rather slowly to changes in membrane potential (MP), has been widely used in flow cytometry (11), the usefulness of DiBAC4 (3) in the pharmacological assay of ion channel modulators has been reported recently in the measurements of membrane hyperpolarization induced by the activation of ATP-dependent K + (KATP) channels (12) and in the assay of KATP channel openers (13). The usefulness of DiBAC4 (3) to assay the potency of BK channel modulators in the system, where recombinant BK channels are heterologously expressed, has not been determined yet.…”
Section: +mentioning
confidence: 99%
“…The activity of hydroxyhexamide can be rationalized by comparison with other members of the sulfonylurea class of drugs. Tolbutamide, chlorpropamide, and tolazemide possess Pharmacologically Active Metabolites 609 similar structures, with a site of structural variation being on the 4-position of the central phenyl ring, which is the site of reduction of acetohexamide to hydroxyhexamide (Gopalakrishnan et al, 2000) (Fig. 40).…”
mentioning
confidence: 99%